Isolated Tubal Torsion in a Term Pregnancy: Case Report and Systematic Review of Literature of the Last 10 Years - Gulino, Ferdinando Antonio; Ettore, Carla; Morreale, Gianfranco; Siringo, Stefano; Russo, Emanuele; D'Asta, Marco; Cannone, Francesco; Ettore, Giuseppe (Frontiers in Surgery, 2022)
Objective Isolated torsion of a fallopian tube is a rare event and it is extremely difficult to be diagnosed in pregnancy. The aim of this study is to present a clinical case report that occurred in our department and to summarize the latest evidence about tubal torsion in pregnancy. Methods We reported data, ultrasonographic features and an intra-operative image of a case report of tubal torsion in a term pregnancy. Then a review of the literature was performed following the PRISMA statement: we searched all the articles related to tubal torsion in pregnancy in the last ten years from the international electronic bibliographic database PUBMED. We collected data regarding population characteristics, clinical features, treatment, and feto-maternal outcomes. Results According to our search strategy, 10 articles were included. The main clinical symptoms were abdominal pelvic pain (100%), nausea, and vomiting (30%). The mean gestational age at the diagnosis was 36 weeks after the last menstrual period in 50% of cases. Ultrasound images showed a cystic lesion in the adnexal area in 70% of cases. In most of the cases, a cesarean section with a contextual salpingectomy was performed. No cases of maternal and fetal death were respectively reported. Conclusion Isolated torsion of the fallopian tube is a rare obstetric condition but it should be considered in case of acute lower abdominal pain presentation during pregnancy. Depending on gestational age, surgical treatment as soon as possible could prevent a salpingectomy.